Analisa Kelayakan Runway Edge Light (Studi Kasus Bandara Rendani Manokwari): Analysis of Feasibility for Runway Edge Light (Case Study in Rendani Airport of Manokwari) - Henny A.B . Lesnussa; Abdul Z. Patiran; Gilang C. Pratama (JISTECH: Journal of Information Science and Technology, 2023)
CCR as an important component of runway edge light that functions to regulate a constant fixed current at each lamp load with the level of lighting divided into five levels. The electrical system on the runway light is one of the applications of electrical science that uses the basic CCR components that can produce constant current. This runway edge light electrical system is assembled using two final circuits installed in series with the intention that if one of the circuits goes out, the other system can still function, The electrical system on the runway edge light is one of the applications of electrical science that uses the basic CCR components that can produce constant current. The Electrical system of the runway edge light is designed and planned with the use of light intensity that can be seen from all angles at a sufficient height, so as to give instructions to the aviator at the time of landing or take-off, and the light intensity used, the current density for the cable is usually the maximum used is 20 A/mm2, and the cross-sectional area of the cable used is 1x6 mm2 with the current passing through the circuit is 6,6 Amperes, so that a current density of 1,1 A/mm2 is obtained.